A rationale for repealing the 1987 Groceries Order - Walsh, Patrick Paul; Whelan, Ciara (Economic & Social Studies, 1999)
A ban on pricing below cost was implemented under the 1987 Groceries Order based on the premise that loss leading used in multi-product retail pricing distorts competition and exploits consumers in the short run, while driving a more concentrated structure and reducing welfare in the long run. Loss leading is examined for multi-product retailers selling in imperfectly competitive market niches with imperfect consumer information. We develop a theoretical argument in a simple two-stage framework that illustrates how loss leading on a subset of products is an equilibrium outcome of price competition that leaves overall welfare equal to that observed under laissez faire.
Keywords: Retail pricing; Groceries Order; Price competition; Laissez faire; Loss leading